Flexibilização dos direitos do trabalho no Brasil: análise a partir da reforma trabalhista do governo Michel Temer - Dantas, Bruna Hávilla Lino (2020)
The present study had as object of research the changes in labor legislation during President Michel Temer's government (2016-2018). The main objective was to analyze the particularities of this changes in labor legislation, in the context of increasing of informal work in Brazil. Theoretical assumptions refer to the Marxist tradition, with elaborations demarcated in the field of labor. Considering the totality, the text also dialogues with works that deal with neoliberalism, the crisis of capitalism and the Brazilian crisis that has developed since 2013. This way, we strive to reflect on labor, informal and intermittent, and brazilian political and economic crisis. The empirical basis of our study was the body of Law 13.467 / 2017 known as "labor reform", data from the National Household Sample Survey - Continuous PNAD from IBGE, DIEESE and IPEA related to unemployment, occupancy rate, average earnings and activity sector, between 2015-2018. The result highlighted informal work as a growing trend in Brazil, and the duality between overexploitation and underutilization of the workforce. The "Labor reform", as a State action, is available to employers, to ensure the increase of capitalist accumulation and relieve the responsibilities and “constraints” of hiring. It also recognizes forms of insertion, especially the intermittent employment contract, evidenced by the intense precariousness of work.